2005
DOI: 10.1158/1055-9965.epi-04-0632
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Melanoma by Body Site

Abstract: It has been hypothesized that cutaneous melanoma at different anatomic sites develops through divergent pathways. We examined this hypothesis prospectively. We followed 152,949 women and 25,204 men free of cancer at baseline for up to 14 years in three large prospective studies. We examined risk factors for melanoma by anatomic location (head or neck, trunk, upper extremity, and lower extremity). Polytomous logistic regression was used to test the difference among risk factors by location of melanoma. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
95
2
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(117 citation statements)
references
References 22 publications
17
95
2
3
Order By: Relevance
“…22,23 Cho et al 15 similarly reported that ''family history'' was associated with increased risks for CM at all sites.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 Cho et al 15 similarly reported that ''family history'' was associated with increased risks for CM at all sites.…”
Section: Epidemiologymentioning
confidence: 99%
“…Another purpose of the study was to evaluate the risk factors possibly associated with primary tumor sites, based on the theories of divergent pathways to melanoma. 8,12,13,[15][16][17] …”
mentioning
confidence: 99%
“…After a review of the study abstracts, we retrieved 80 articles for further assessment, of which 2 reports of cohort studies (9,10), and 47 from case-control studies (refs. 4, 5, 7, 11-54; total = 49) met the eligibility criteria (Fig.…”
Section: Literature Searchmentioning
confidence: 99%
“…Common nevi A total of 31 studies provided data on the association between common nevi (whole-body count) and melanoma. An additional eight case-control studies (14,24,32,34,35,39,40,49) and one cohort study (9) did not report on whole-body nevus counts, but rather specific body sites including the arms or legs. A further six studies presented data only for palpable and/or large common nevi (13,19,28,30,31, and 44) and one study did not use quantitative common nevus counts (27); these were also excluded from the analyses (Fig.…”
Section: Atypical Nevimentioning
confidence: 99%
“…Recent studies suggest MM of the head and neck is more strongly related to sunburn, and of the trunk to more chronic sun exposure. 28,29 People with fair skin, blue eyes, fair or red hair and those who burn easily are at increased risk of MM, as are those with freckling and benign naevi, especially those with more than 100 such lesions. Large or giant congenital melanocytic lesions confer a high risk, as does the presence of any atypical or dysplastic naevi, or if MM itself has previously occurred.…”
Section: Investigations and Treatmentmentioning
confidence: 99%